Maskulinitas dan Feminitas dalam Al-Qur’an: Analisis Tafsir Tematik Gender dan Implikasinya dalam Wacana Islam Kontemporer - Ende Hasan Albana; Rahendra Maya (Ikatan Dai Indonesia, 2026)
The issue of the relationship between men and women remains a continuously evolving theme in contemporary Islamic discourse, particularly concerning gender constructions and their relevance to modern social dynamics. The discrepancy between the normative ideals of the Qur'an and certain interpretative practices influenced by patriarchal culture necessitates a more comprehensive and contextualized reinterpretation. This study aims to analyze the essence of the creation of men and women, examine the theological constructions of masculinity (al-rajūlah) and femininity (al-unūthah) in the Qur'an, and formulate a gender relations paradigm based on the principle of takāmul (complementarity). This research employs a qualitative approach based on library research using the thematic exegesis (tafsīr mawḍū‘ī) method by collecting, classifying, and analyzing Qur'anic verses related to gender, supported by both classical and contemporary exegetical literature. The findings reveal that the Qur'an positions men and women equally in terms of humanity, spirituality, and moral responsibility, as reflected in the concepts of nafs wāḥidah (a single origin), karāmah insāniyyah (human dignity), and piety as the ultimate criterion of virtue. Masculinity, from the Qur'anic perspective, is not understood as male superiority but rather as an ethical responsibility encompassing leadership, integrity, and protection. Meanwhile, femininity is understood as the embodiment of compassion, chastity, wisdom, and social contribution that extends beyond the domestic sphere. This study concludes that gender relations in Islam are founded upon the principle of mutual complementarity rather than domination or subordination, thereby providing a conceptual foundation for developing a more just, proportional, and socially responsive contemporary Islamic discourse.